2015
DOI: 10.1016/j.physbeh.2015.04.042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of histidine on mental fatigue and cognitive performance in subjects with high fatigue and sleep disruption scores

Abstract: Our previous study reported that a dried bonito broth known in Japan as 'dashi' improved or ameliorated mood states, including fatigue, during the daily lives of human subjects. Histidine is an amino acid that is present in dried bonito broth, and we sought to evaluate whether histidine would affect feelings of fatigue in humans. We investigated the effects of histidine intake on the feeling of fatigue, mood states and mental task performance by performing a placebo-controlled, double-blind crossover trial. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 50 publications
(71 reference statements)
0
40
0
1
Order By: Relevance
“…High amounts of HIS (109 mg/g) have been detected in dried bonito broth, a food ingredient used commonly in Japanese meals, called dashi. Bonito (skipjack tuna; Katsuwonus pelamis) is commonly consumed fish; dried bonito broth is used more frequently than beef or chicken bouillon for soup stock [34].…”
Section: Requirements and Sources Of Dietary Hismentioning
confidence: 99%
See 2 more Smart Citations
“…High amounts of HIS (109 mg/g) have been detected in dried bonito broth, a food ingredient used commonly in Japanese meals, called dashi. Bonito (skipjack tuna; Katsuwonus pelamis) is commonly consumed fish; dried bonito broth is used more frequently than beef or chicken bouillon for soup stock [34].…”
Section: Requirements and Sources Of Dietary Hismentioning
confidence: 99%
“…Increased HIS intake in the form of a dried bonito broth has improved mood state and mental task performance of human subjects [33,34,36]. Several studies have reported an anorectic effect of HIS administration [65][66][67][68] and HIS-enriched diet [62][63][64].…”
Section: Effects Of Dietary His On Histamine Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Talvez isso possa ser explicado pela ausência do farmacêutico, em 62.2% das coletas noturnas, e pela sobrecarga de trabalho do técnico, que nesse caso era o único colaborador na farmácia, dificultando a realização de todas as atividades necessárias. A sobrecarga é o principal fator apontado por farmacêuticos e técnicos em outras pesquisas [13][14][15] e a privação do sono em trabalhos noturnos pode levar à fadiga e, consequentemente, a uma diminuição do desempenho, da atenção e do tempo de reação; aumentando, assim, a vulnerabilidade a erros 5 .…”
Section: Discussionunclassified
“…The former might be related to memory lapses 10. Factors such as fatigue, sleep disruption and distraction may interfere with working memory and cause dispensing errors 11–13.…”
Section: Discussionmentioning
confidence: 99%